Overview of Nurses' Knowledge of Hand Hygiene in Implementing Patient Safety in Intensive Care Units - Moecharam, Moecharam; Nursalam, Nursalam; Ahsan, Ahsan; Misutarno, Misutarno (Indonesian Academia Health Sciences Journal, 2022)
Hand hygiene is a simple step that is effective in reducing infection rates, but is often overlooked by health workers. Low hand hygiene in health workers is partly influenced by health workers' ignorance of how hands can be contaminated and ignorance of the importance of hand hygiene in reducing the spread of infection. This study aims to explore nurses' knowledge of hand hygiene in intensive care units. Methods: This study used a qualitative study design with a phenomenological approach. This study involved 15 clinical nurse supervisors who were interviewed in-depth using semi-structured interview guidelines with inclusion criteria: aged 25-45 years, being a clinical supervisor in the room, work experience> 8 years. Data from in-depth interviews were transcribed and data were analyzed using the Van Mannen analysis method. Results: Knowledge of hand hygiene nurses is based on: understanding of germ transmission, so that nurses are able to prevent transmission and accompanied by regulations on the implementation of hand hygiene which are guidelines for its implementation. Conclusion: Clinical nurse supervisors in hand hygiene are based on knowledge, social support and behavior in implementing hand hygiene. The implications of the results of this study are information in efforts to improve the fulfillment of hand hygiene so that in meeting health needs, they not only meet patient needs but also pay attention to the risk of germ transmission.